God and the meanings of life : what God could and couldn't do to make our lives more meaningful - Mawson, T. J. (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2016)
Some philosophers have thought that life could only be meaningful if there is no God. For Sartre and Nagel, for example, a God of the traditional classical theistic sort would constrain our powers of self-creative autonomy in ways that would severely detract from the meaning of our lives, possibly even evacuate our lives of all meaning. Some philosophers, by contrast, have thought that life could only be meaningful if there is a God. God and the Meanings of Life is interested in exploring the truth in both these schools of thought, seeking to discover what God could and couldn't do to make life meaningful (as well as what he would and wouldn't do). Mawson espouses a version of the 'amalgam' or 'pluralism' thesis about the issue of life's meaning - in essence, that there are a number of different legitimate meanings of 'meaning' (and indeed 'life') in the question of life's meaning. According to Mawson, God, were he to exist, would help make life meaningful in some of these senses and hinder in some others. He argues that whilst there could be meaning in a Godless universe, there could be other sorts of meaning in a Godly one and that these would be deeper.